PERILAKU PEMILIH MASYARAKAT ADAT DESA KAKARA PADA PEMILUKADA MALUKU UTARA 2018 - Gloria Miagina Palako Djurubassa; Herman Sidete (Universitas 17 Agustus 1945 Jakarta, 2020)
This research is about voting behaviour of indigenous people at Kakara Village in North Mollucas election 2018. On the previous Governor election in 2013 and Regent election in 2015, typologhy of North Mollucas Voter is traditional voter category and most of them spread to littoral and inland villages. This research be doing at Kakara village with purpose to reveal how is voting behavior of indigenous people at Kakara village to vote their governor and vice governor, and the causes of it. The method of this research is qualitative which is to explain and describe the facts of voting behavior of indigineous people as voter. Design of this research is case study with the research object such as important people in the custom, community, religion, and some of people at Kakara village. Collecting data technique be doing by observation, sharing questionnaire and deep interview to some of respondence by choosing as purposive to get data about social structure of indigineous people, identification of voting behavior and mass base of candidate. Voting behavior of indigineous people at Kakara village as a traditional voter when to deal with black campaign, identity issue, and religious issue certainly will be implicated to their choice in Governor and vice governor election. This is the interesting point that make this research should be investigated because voting behavior especially in North Halmahera always changed since election in 2015. The result of this research can be used as a basic by government, political party and academic to take policy as a problem solution to Indigineous People at Kakara Village.